La curva de dilución en el estudio de las derivaciones arteriovenosas centrales - Cazorla Tálleri, Alberto (1953)
Dilution curve of the dye T-1824 has been studied in eleven patients with central arteriovenous shunts; also in a case of venous-arterial bypass; one carrying an abdominal aortic aneurysm; a patient in congestive heart failure before and during treatment, and two normal subjects in whom errors in technique (puncture of the femoral vein; injection rebound) was committed.